2021
DOI: 10.5897/ajar2021.15690
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and seed physiological quality changes during seed development and maturation in African eggplant (Solanum aethiopicum L.)

Abstract: This work aimed at determining the optimum harvest time of African eggplant (Solanum aethiopicum L.) seeds, cv. Oforiwa and cv. Kpando for maximum physiological seed quality under tropical (TCC) and temperate oceanic climatic (TOC) conditions. Fruit morphological metrics such as fruit weight and size were also related to seed physiological quality. Seeds were harvested at different maturation stages from 20 to 82 days after anthesis (DAA). Seed quality was assessed according to moisture content, dry seed weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
0
0
1
Order By: Relevance
“…Several studies on seed development and maturation have revealed that seeds of some species attain germination potential very early just few days after anthesis but some requires sometime in order to attain the ability to germinate. This variation exists even within the same species as observed in two species of S. aethiopicum, Oforiwa and Kpando [36]. However, as discussed previously, it is also possible to harvest seeds one or two weeks before physiological maturity and give them a period of after ripening to attain full maturity and hence good germination and vigor, particularly for those borne in fleshy fruits [54].…”
Section: Seed Development and Maturation Effects On Physiological See...mentioning
confidence: 75%
See 3 more Smart Citations
“…Several studies on seed development and maturation have revealed that seeds of some species attain germination potential very early just few days after anthesis but some requires sometime in order to attain the ability to germinate. This variation exists even within the same species as observed in two species of S. aethiopicum, Oforiwa and Kpando [36]. However, as discussed previously, it is also possible to harvest seeds one or two weeks before physiological maturity and give them a period of after ripening to attain full maturity and hence good germination and vigor, particularly for those borne in fleshy fruits [54].…”
Section: Seed Development and Maturation Effects On Physiological See...mentioning
confidence: 75%
“…However, this seems to be affected by genotype as [60,61] obtained contrasting results in antioxidant enzyme activity trends in the same crop. High antioxidant enzyme activity during early seed development has been reported in African eggplant [62] and Hevea brasiliensis L [63]. Both authors reported a decline after an early increase, and increase at the end of the seed maturation phase.…”
Section: Changes In Biochemical Seed Quality During Seed Development ...mentioning
confidence: 92%
See 2 more Smart Citations
“…Las semillas obtenidas de frutos maduros tienen capacidad de germinar, sin embargo, tienen menor velocidad de germinación (Figura 6) y la emergencia tiende a ser menor que la semilla cosechada de frutos menos maduros (Figura 8), es probable que las semillas obtenidas de los frutos maduros hayan comenzado a presentar deterioro, pues la madurez fisiológica de la semilla pudo haber sido alcanzada en los estados de maduración anteriores (Botey et al, 2021). Este comportamiento resultó diferente a los resultados de Cavero et al (1995), quienes encontraron mejores resultados en la germinación de las semillas extraídas de frutos completamente maduros a los que se les permitió madurar en exceso.…”
Section: Resultados Y Discusiónunclassified